An in vivo biosensing, biomimetic electrochemical transistor with applications in plant science and precision farming. Issue 1 (December 2017) - Coppedè, Nicola; Janni, Michela; Bettelli, Manuele; Maida, Calogero; Gentile, Francesco; Villani, Marco; Ruotolo, Roberta; Iannotta, Salvatore; Marmiroli, Nelson; Marmiroli, Marta; Zappettini, Andrea
Abstract Thein vivo monitoring of key plant physiology parameters will be a key enabler of precision farming. Here, a biomimetic textile-based biosensor, which can be inserted directly into plant tissue is presented: the device is able to monitor, in vivo and in real time, variations in the solute content of the plant sap. The biosensor has no detectable effect on the plant's morphology even after six weeks of continuous operation. The continuous monitoring of the sap electrolyte concentration in a growing tomato plant revealed a circadian pattern of variation. The biosensor has the potential to detect the signs of abiotic stress, and therefore might be exploited as a powerful tool to study plant physiology and to increase tomato growth sustainability. Also, it can continuously communicate the plant health status, thus potentially driving the whole farm management in the frame of smart agriculture.